Job satisfaction and well-being among deaf and hard of hearing employees in Iceland - Þóra Ósk Böðvarsdóttir 1989- (2017)
Approximately 360 million individuals worldwide have auditory difficulties. Studies have shown that many individuals who are deaf or hard of hearing experience communicational and occupational barriers that may negatively affect their occupational advancement. Due to limited researches, this study was conducted to examine the job satisfaction and well-being among employees who are deaf and hard of hearing in Iceland. Differences between experiences of employees who are deaf and employees who are hard of hearing wereas also examined. A sample of 46 individuals with auditory difficulty, 10 males and 36 females, was used. A survey based on the Icelandic version of the QPSNordic questionnaire for psychological and social factors at work and the Amsterdam Checklist for Hearing and Workk, was used to examine the participant´s experiences at work. The results indicated that employees who are deaf and hard of hearing receive much social support. Employees who are deaf experience more discrimination than employees who are hard of hearing, but there was not a difference between the two groups in experiencing psychological strain, and job satisfaction. Um 360 milljónir einstaklinga glíma við heyrnarörðugleika. Erlendar rannsóknir hafa sýnt fram á að margir einstaklingar sem eru Döff eða heyrnarskertir upplifa samskiptarörðugleika og hindranir í atvinnulífinu sem gæti haft neikvæð áhrif á starfsframa þeirra. Rannsókn þessi var framkvæmd í ljósi þess að fáar sem engar rannsóknir hafa verið gerðar hérlendis á upplifun Döff og heyrnarskertra einstaklinga á vinnumarkaði. Munur á milli upplifun starfsmanna sem voru Döff og starfsmanna sem voru heyrnarskertir var skoðaður. Úrtakið samanstóð af 46 einstaklingum sem glíma við heyrnarörðugleika, þar af voru 10 menn og 36 konur. Könnun byggð á QPSNordic spurningarlistanum um sálfélagslega þætti í vinnu og Amsterdam Checklist for Hearing and Work var notuð til að skoða upplifun þátttakenda í starfi. Niðurstöður bentu til þess að Döff og heyrnarskertir starfsmenn upplifi almennt ...